DIAGNOSTIC IMAGING AND ENDOSCOPY OF THE SCHNAUZER DOG WITH UPPER GASTROINTESTINAL TRACT DISORDERS - Deni Noviana; Kholis Afidatunnisa; Annisa Rofiqoh Syafikriatillah; M. Fakhrul Ulum; Gunanti Gunanti; Siti Zaenab (Jurnal Kedokteran Hewan, 2017)
The aim of this study was to describe the role of diagnostic imaging and endoscopy to define the diagnose of the upper gastrointestinal tract disorder of the Schnauzer. The information from the owner stated that the dog has been vomiting for a year, sometimes containing blood. There might also be a possibility that it had eaten a corpus alienum. This case study covered physical examination, hematology and blood chemical analysis, diagnostic imaging radiography and ultrasonography as well as endoscopy performed. Physical examination showed weight loss and anorexia. Hematology and blood chemical analysis showed an increase in hemoglobin, hematocrit, lymphocyte, ureum, creatinine, alanine aminotransferase (ALT), and alkaline phosphatase (ALP) values. Abdominal radiograph showed no abnormality in the abdominal organs. Abdominal ultrasonography showed a hiperechoic elongated mass attached on the stomach mucosal surface which forms an acoustic shadowing at the ventral.  Endoscopy showed pathological lesions that is inconsistency of stomach mucosa surface, foamy fluid in the stomach, ulcers and erosion of the stomach mucosal surface. Based on the diagnostic imaging and endoscopy performed, the animal was clearly diagnosed with chronic gastritis accompanied by stomach ulcer and erosion.